Prevalence of Nicotinic Stomatitis in Smokers Attending Oral Diagnosis Department in Khanzad Dental Center and Hawler Medical University –College of Dentistry - Qasim Nsaif , Noor; Qader, Jamal; Al.zubaidee, Ali (Diyala Journal of Medicine, 2023)
Background: Tobacco smoking is considered as one of the most common risk factors for development of oral mucosal lesions which may carry a potential risk for development of oral cancer. Objective: To find the prevalence of nicotinic stomatitis in a sample of cigarette and water pipe smokers in Erbil city of Iraq. Patients and Methods: This study included 410 smokers aged 18 years and above who are smoking for at least five years. Cigarette, water pipe and dual smokers were included of both genders. The type, duration and frequency of habit were recorded. The diagnosis of nicotinic stomatitis was done clinically. The data entered and analyzed by (SPSS software 25th version). Results: Majority of participants were cigarette smokers (73.7%).Out of 410 smoker, prevalence of nicotinic stomatitis was (55.3%) in cigarette smokers,(24.6%) in dual smokers while none of water pipe users developed nicotinic stomatitis ;the incidence increase with increase in duration and frequency of the habit. Conclusion: In this study we found cigarette smoking was more commonly practiced than water pipe .Nicotinic stomatitis is more prevalent in cigarette smoking and its incidence increased with duration and frequency of the habit.